International Olympic Committee consensus statement on thermoregulatory and altitude challenges for high-level athletes. Issue 11 (9th June 2012) - Bergeron, MF; Bahr, R; Bärtsch, P; Bourdon, L; Calbet, JAL; Carlsen, KH; Castagna, O; González-Alonso, J; Lundby, C; Maughan, RJ; Millet, G; Mountjoy, M; et al.
Abstract : Challenging environmental conditions, including heat and humidity, cold, and altitude, pose particular risks to the health of Olympic and other high-level athletes. As a further commitment to athlete safety, the International Olympic Committee (IOC) Medical Commission convened a panel of experts to review the scientific evidence base, reach consensus, and underscore practical safety guidelines and new research priorities regarding the unique environmental challenges Olympic and other international-level athletes face. For non-aquatic events, external thermal load is dependent on ambient temperature, humidity, wind speed and solar radiation, while clothing and protective gear can measurably increase thermal strain and prompt premature fatigue. In swimmers, body heat loss is the direct result of convection at a rate that is proportional to the effective water velocity around the swimmer and the temperature difference between the skin and the water. Other cold exposure and conditions, such as during Alpine skiing, biathlon and other sliding sports, facilitate body heat transfer to the environment, potentially leading to hypothermia and/or frostbite; although metabolic heat production during these activities usually increases well above the rate of body heat loss, and protective clothing and limited exposure time in certain events reduces these clinical risks as well. Most athletic events are held at altitudes that pose little to no health risks; and training exposures are typically brief and well-tolerated. While these and other environment-related threats to performance and safety can be lessened or averted by implementing a variety of individual and event preventative measures, more research and evidence-based guidelines and recommendations are needed. In the mean time, the IOC Medical Commission and International Sport Federations have implemented new guidelines and taken additional steps to mitigate risk even further.